2013
DOI: 10.1080/09712119.2012.739093
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of free radicals in parasitic infestations

Abstract: The amount of reactive oxygen species increased in cells of hosts infected with parasites as reported by a number of studies. The excess of free radicals in the parasitised cells depends on the nutritional status of the host, the degree of parasitic infestations and on the destructive effect on tissue, and reported associating blood parasites like Theileriosis, Babesiosis and Trypanosomosis. In addition, external parasites and endoparasites such as Fasciola sp., Trichostrongylus sp. and Eimeria sp. had been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 81 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…Oxidative stress has been reported to be involved in the pathogenesis of several diseases including parasitic infections [90]. Cellular metabolism produces reactive oxygen species (ROS) and reactive nitrogen species (RNS) [91].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been reported to be involved in the pathogenesis of several diseases including parasitic infections [90]. Cellular metabolism produces reactive oxygen species (ROS) and reactive nitrogen species (RNS) [91].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the functional importance of this effect is currently unclear. Previous studies have reported that early infection with parasitic worms generates NO and H 2 O 2 production by eosinophils and MΦs in the peritoneal cavity (Abd Ellah, 2013 ; Jedlina et al., 2011). Targeting the redox system in favor of ROS induction might therefore be one of the mechanisms by which worms accelerate the repair of damage (Dunnill et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Se-yeast supplementation increased gene expression of the selenocysteine-containing selenoproteins glutathione peroxidase-4 [31], which is vital for the detoxification of lipid hydroperoxide free radicals in the intestinal mucosa [40], and selenoprotein S1 [31], which has been hypothesized to play a role in the detoxification of lipid hydroperoxide free radicals in the intestinal mucosa [41,42]. Intestinal parasitism has been reported to be associated with increased formation of lipid hydroperoxides [43]. Thus, we were interested in whether the potentially beneficial changes in gene expression in WB neutrophils translated into decreased GI parasite loads.…”
Section: Discussionmentioning
confidence: 99%